KOMUNIKASI DAKWAH KH. MOCH. IMAM CHAMBALI DALAM TAYANGAN “PADHANGE ATI” JTV SURABAYA 2015 - Noor Rahmah (An-Nida : Jurnal Komunikasi Islam, 2016)
Da'wah is very dependent on communication. Submission of da'wah needs the existence of forms, processes and communication techniques for the success of these activities. The event "Padhange Ati" in JTV Surabaya is one of the programs that raised the da'wah preaching filled by preachers from East Java KH. Moch. Imam Chambali and also a presenter Abah Topan. The program is one of the da'wah media communication. The purpose of this study is to find out how the communication propagation KH. Moch. Imam Chambali in the show "Padhange Ati Blusukan" JTV Surabaya. This type of research is descriptive qualitative. Data collection by observing form, process and communication technique of da'wah in three video Padhange Ati Blusukan, then analyzed descriptively qualitative. The result of this research is the form of communication of da'wah done by KH. Moch. Imam Chambali is a small group communication and mass communication of television media. KH. Moch. Imam Chambali uses the primary communication process using symbols of language and gestures. The communication technique used is persuasive communication in the form of arrangement, integration and reward, and informative communication which is in the definition, description and demonstration.